Algorithm of determination of the volume of surgical intervention in athletes with Haglund deformity - M. N. Velichko; A. M. Belyakova; D. V. Volchenko; А. S. Domozhirova; A. Yu. Terskov; A. P. Sereda; A. S. Samoilov (National Electronic Information Consortium (NEICON), 2020)
Objective: to develop an algorithm for determining the extent of surgical intervention for pain in the heel region based on a comprehensive clinical and instrumental assessment of the functional state of the lower extremities. Materials and methods: during the examination of 18 athletes with pain in the heel area, we used a thermal imaging examination (at rest and after exercise) in combination with magnetic resonance imaging data. Infrared thermography was performed using an infrared camera. Data analysis was carried out using the specialized online service tvision.pro, which allows you to track the dynamics of the patient's thermographic picture. The combination of images of thermographic and MRI studies makes it possible to assess the functional state of the structures of the heel region with the identification of the structures most involved in the pathological process. Results: based on the experience of treating athletes with pain in the heel area, we developed an algorithm for determining the extent of surgical intervention for Haglund deformity. The algorithm is based on the analysis of MRI data and their comparison with the results of the examination of the soft tissue of the heel area using functional thermal imaging. Conclusions: a comprehensive analysis of the data of thermographic and tomographic studies allows you to perform an objective assessment of the functional state of the patient based on the primary localization of the pathological process. The developed algorithm is applicable for planning the extent of surgical intervention and making a choice of preferable technique. The proposed tactic contributes to early return to competitive load. The infrared thermography technique provides important additional data on the functional state of the athlete's musculoskeletal system. It is absolutely safe for both the patient and the specialist who conducts the study.